Endovascular retrograde approach may be a better option for acute tandem occlusions stroke. Issue 2 (April 2019) - Yang, Dong; Shi, Zhonghua; Lin, Min; Zhou, Zhiming; Zi, Wenjie; Wang, Huaiming; Hao, Yonggang; Guo, Fuqiang; Liu, Wenhua; Xu, Gelin; Xiong, Yunyun; Liu, Xinfeng
Objective: The endovascular treatment strategy for acute tandem occlusion stroke is challenging, and controversy exists regarding which lesion should be treated first. This study addresses the uncertainty regarding the priority choice for thrombectomy in acute anterior circulation tandem occlusion stroke. Methods: We analysed the clinical and angiographic data of tandem stroke patients who underwent interventional therapy from the endovAsCular Treatment of acUte Anterior circuLation ischaemic stroke (ACTUAL) registry. Recanalisation was assessed according to the modified thrombolysis in cerebral infarction score. Clinical outcome was evaluated at 90 days using the modified Rankin scale score. Results: Sixty tandem occlusion stroke patients were enrolled. Thirty-one (51.7%) patients received anterograde therapy, while 29 (48.3%) patients underwent the retrograde approach. Successful recanalisation (modified thrombolysis in cerebral infarction score 2b–3) occurred in 78.3% (47/60) of patients, and 50.0% (30/60) of patients achieved a modified Rankin scale score of 0–2 at 90 days. Patients undergoing the retrograde approach spent less time in distal occlusion recanalisation (125 (86–167) vs. 95 (74–122) minutes; P  = 0.04) and achieved better functional outcomes at 90 days (69.0% (20/29) vs. 32.3% (10/31); P  = 0.004) than patients who received anterograde therapy. The retrograde approach was associated with favourable clinical outcomes (odds ratio 0.21; 95% confidence interval 0.07–0.64; P  = 0.006). Conclusion: For acute tandem occlusion stroke, favourable outcomes were better in patients undergoing retrograde therapy than in patients who received the anterograde approach. Future randomised trials are warranted to determine the optimal treatment.